Transformation of the legal nature of digital assets in the context of real-world asset tokenization - Leshchenko, Yulia (Академічні візії, 2024)
The relevance of the study is determined by the rapid development of distributed ledger technologies and the growing use of tokenization mechanisms in property and financial relations. The tokenization of real-world assets creates new models for the circulation of rights to tangible and intangible property while simultaneously raising questions regarding the legal nature of digital assets and the protection of tokenized rights. The purpose of the article is to develop a comprehensive understanding of the transformation of the legal nature of digital assets in the context of real-world asset tokenization and to substantiate approaches to the legal recognition and protection of tokenized property rights. Methods include system analysis, comparative legal analysis, the formal legal method, and the generalization of scientific approaches. The study investigates the conceptual foundations of digital assets, analyzes legal mechanisms and models of asset tokenization, and identifies the transformation of ownership, transfer, and disposal rights in digital environments. It is established that tokenization enhances asset liquidity, expands investment opportunities, and creates new forms of rights management. Key challenges include legal uncertainty, regulatory fragmentation, jurisdictional complexity, and insufficient protection of token holders. The findings confirm that tokenization is transforming traditional property relations and requires the development of coherent, technology-neutral regulatory frameworks. Future research should focus on cross-border legal issues, digital ownership in decentralized ecosystems, smart contract liability, and international approaches to the protection of tokenized rights.